Synthesis of protocol entities specifications from service specifications in a Petri net model with registers - Yamaguchi, H.; Okano, K.; Higashino, T.; Taniguchi, K. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
In general, the services of a distributed system are provided by some cooperative protocol entities. The protocol entities must exchange some data values and synchronization messages in order to ensure the temporal ordering of the events which are described in a service specification of the distributed system. It is desirable that a correct protocol entity specification for each node can be derived automatically from a given service specification. In this paper, we propose an algorithm which synthesizes a correct protocol entity specification automatically from a service specification in a Petri Net model with Registers called PNR model. In our model, parallel events and selective operations can be described naturally. The control flow of a service specification must be described as a free-choice net in order to simplify the derivation algorithm, however, many practical systems can be described in this class. In our approach, since each protocol entity specification is also described in our PNR model, we can easily understand what events can be executed in parallel at each protocol entity.